IN VITRO BIOACTIVITY TEST OF IRRADIATED MAHKOTA DEWA BARK [Phaleria macrocarpa (Scheff.) Boerl.] AGAINST HUMAN CANCER CELL LINES - Ermin Katrin Winarno (Universitas Gadjah Mada, 2012)
Gamma irradiation has been used to preserve an herbal medicine, but it has not been known the effects of gamma irradiation on their bioactivity as an anticancer agent yet. In the previous study, the gamma irradiation on mahkota dewa bark with the optimum dose of 7.5 kGy could be used for decontamination of bacteria and fungus/yeast. In this report, the effect of gamma irradiation with the dose of 7.5 kGy on the bioactivities of mahkota dewa (Phaleria macrocarpa (Scheff) Boerl.) bark against leukemia L1210 cells was studied. The control and irradiated samples were successively macerated with n-hexane and ethyl acetate. In the previous results, silica gel column chromatography of ethyl acetate extract of non irradiated sample (control) gave 8 fractions. Among these fractions, fraction 6 indicated the most cytotoxic-potential fraction, so that in this experiment, the ethyl acetate extract of irradiated and non irradiated sample were fractionated with the same manner as previous fractionation. The fraction 6 obtained both from control and irradiated samples were then assayed their inhibitory activities against 4 kinds of human cancer lines, i.e. HeLa, THP-1, HUT-78 and A-549. The results showed that the fraction 6 from control sample gave IC50 values of 3.65, 5.59, 3.55, and 4.06 µg/mL, against HeLa, THP-1, HUT-78 and A-549, respectively, meanwhile fraction 6 from irradiated sample gave IC50 values of 8.26, 7.02, 5.03, and 5.59 µg/mL, respectively. Gamma irradiation dose of 7.5 kGy on mahkota dewa bark could decreased the cytotoxic activity of fraction 6 as the most cytotoxic-potential fraction against HeLa, THP-1, HUT-78 and A-549 cancer cell lines, but decreasing the cytotoxic activity has not exceeded the limit of an extract and the fraction declared inactive. So that the irradiation dose of 7.5 kGy can be use for decontamination of bacteria and fungus/yeast without eliminating the cytotoxic activity.